The IAT shows no evidence for Kandinsky's color-shape associations - Makin, Alexis; Wuerger, Sophie (Frontiers in Psychology, 2013)
In the early 20th century, the Bauhaus revolutionised art & design by using simple colours and forms. Wassily Kandinsky was especially interested in the relationship of these two visual attributes and postulated a fundamental correspondence between colour and form: yellow triangle, red square and blue circle. Subsequent empirical studies also used preference judgments to test Kandinsky’s original colour-form combinations, usually yielding inconsistent results. We have set out to test the validity of these postulated associations by using the Implicit Association Test. Participants pressed one of two buttons on each trial. On some trials they classified shapes (e.g. circle or triangle). On interleaved trials they classified colours (e.g. blue or yellow). Response times should theoretically be faster when the button mapping follows Kandinsky’s associations: For example, when the left key is used to report blue or circle and the right is used for yellow and triangle, than when the response mapping is the opposite of this (blue or triangle, yellow or circle). Our findings suggest that there is no implicit association between the original colour-form combinations. Of the three combinations we tested, no response time differences were significantly greater than zero, although there was a marginal effect in one experiment. It can be concluded that our IAT does not support all Kandinsky’s postulated colour-form associations, and these are probably not an aesthetic universal.